Strategic Role of Modern Accounting in Improving Tourism Management Effectiveness - OKTAYANI, Ni Kadek Rita; DEWI, Ni Made Sintya; KEWA, Maria Serliana Ina; PUTRI, Ni Putu Amelia (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose:As global competition becomes increasingly fierce, this sector requires a more effective and efficient managerial approach. Modern accounting, which has now transformed from an administrative tool into a data-based managerial information system, plays a strategic role in supporting more precise and efficient decision-making in tourism management. This article aims to examine the application of modern accounting in the tourism sector, especially in operational cost planning and control, financial accountability, and managerial performance.Methodology:This article uses a library research method, which in its implementation focuses on a literature review of previous research results. Literature studies are conducted by reviewing, understanding, and critically analyzing various scientific literature, especially research journals that discuss the application of modern accounting in improving the effectiveness of tourism management. By integrating management accounting systems, responsibility accounting, and information technology, tourism destination managers can design policies that are more responsive to market changes and consumer demands.Findings:The implementation of modern accounting also contributes to increasing transparency, strengthening the reputation of tourist destinations, and increasing their competitiveness in the global market.Implication:Based on the results of the literature review, the application of modern accounting has been proven to have a positive impact on operational efficiency, financial transparency, and the competitiveness of the tourism industry in Indonesia.